Atmospheric bulk deposition measurements of organochlorine pesticides at three alpine summits. (January 2015) - Jakobi, Gert; Kirchner, Manfred; Henkelmann, Bernhard; Körner, Wolfgang; Offenthaler, Ivo; Moche, Wolfgang; Weiss, Peter; Schaub, Marcus; Schramm, Karl-Werner
Abstract: Bulk deposition samples were collected at three elevated summits in different parts of the Alps from 2005 to 2010. Deposition samples were analyzed for a wide range of organochlorine pesticides (OCPs). HCHs, DDT, DDD, DDE, chlordanes, cis-heptachlor, HCB, dieldrin and endrin were found in all samples, only aldrin was found less frequently. Differences in the mean deposition rates between the three sites reflect the different amounts of precipitation at these sites. At the northern edge of the Alps with the highest annual total precipitations, mean annual deposition rates were at least twice those at the Swiss site for most of the investigated OCP. Average annual deposition of α-HCH amounted to 602, 461 and 216 ng m −2 year −1, the sum of DDT, DDD and DDE to 579, 210 and 144 ng m −2 year −1 and the sum of trans- and cis-chlordane to 35, 47, 16 ng m −2 year −1 at Zugspitze, Sonnblick, and Weissfluhjoch, respectively. A quite distinct seasonal pattern of OPC deposition was observed at all three locations. For most of the HCH isomers, higher deposition rates were observed in summer than in winter at all three sites, which may be caused by enhanced re-volatilization due to higher summer temperatures and the ongoing application of HCH-containing products in some regions as well. For the other investigated OCPs, higher summer deposition rates were found only at Weissfluhjoch. This site is more often affected by air masses crossing the river Po basin than the other two sites, an area exhibiting higher summer temperatures compared to other regions adjacent to the Alps. Highlights: Bulk deposition was sampled at three elevated Alpine sites from 2005 to 2010. Samples were analyzed for organochlorine pesticides (OCPs). Up to 28 OCPs have been detected mostly in all samples at all sites. Deposition rates show regional differences and different seasonal patterns. Deposition in the Alps shows comparable levels like similar altitudes worldwide.